Quantifying Barrovian metamorphism in the Danba Structural Culmination of eastern Tibet - Weller, O; St-Onge, MR; Waters, D; Rayner, N; Searle, M; Chung, S; Palin, R; Lee, Y; Xu, X (2013)
The Danba Structural Culmination is a tectonic window into the late Triassic to early Jurassic Songpan-Garzê Fold Belt of eastern Tibet, which exposes an oblique section through a complete Barrovian-type metamorphic sequence. Systematic analysis of a suite of metapelites from this locality has enabled a general study of Barrovian metamorphism, and provided new insights into the early thermotectonic history of the Tibetan plateau. The suite was used to create a detailed petrographic framework, from which four samples ranging from staurolite to sillimanite grade were selected for thermobarometry and geochronology. Pseudosection analysis was applied to calculate P-T path segments and determine peak conditions between staurolite grade at ∼5.2 kbar and 580 °C and sillimanite grade at ∼6.0 kbar and 670 °C. In situ U-Pb monazite geochronology reveals that staurolite-grade conditions were reached at 191.5 ± 2.4 Ma, kyanite-grade conditions were attained at 184.2 ± 1.5 Ma, and sillimanite-grade conditions continued until 179.4 ± 1.6 Ma. Integration of the results has provided constraints on the evolution of metamorphism in the region, including a partial reconstruction of the regional metamorphic field gradient. Several key features of Barrovian metamorphism are documented, including nested P-T paths and a polychronic field gradient. In addition, several atypical features are noted, such as P-T path segments having similar slopes to the metamorphic field gradient, and Tmax and Pmax being reached simultaneously in some samples. These features are attributed to the effects of slow tectonic burial, which allows for thermal relaxation during compression. While nested, clockwise P-T-t loops provide a useful framework for Barrovian metamorphism, this study shows that the effects of slow burial can telescope this model in P-T space. Finally, the study demonstrates that eastern Tibet experienced a significant phase of crustal thickening during the Mesozoic, reinforcing the notion that the plateau may have a long history of uplift and growth. © 2013 John Wiley and Sons Ltd.